Characterization of Onchidiid Slug (Onchidium typhae) West Kalimantan Waters as Antibacterials and Antifungal - Bambang Wijianto; Hasyrul Hamzah; Annisa Larasati Nurhidayah; Guci Intan Kemuning; Riyadh Aqilsya Amaryl Dyas (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Onchidiid slug (Onchidium typhae) is a nudibranch that coastal communities in West Kalimantan have widely used as wounds. The study aims to characterize the West Kalimantan water O. typhae as antibacterial and antifungal. The study of O. typhae was carried out in several stages: preparation and optimization, extraction by Quinn method, characterization and identification of bioactive compounds, and antibacterial and antifungal assay using the microdilution method. The result of the proximate test showed that O. typhae powder contains high protein, namely 67.68%. Phytochemical screening results from methanol, ethyl acetate, and chloroform extracts contain alkaloids and amino acids. Methanol, chloroform, and ethyl acetate extract 1% of O. typhae showed inhibitory activity against Staphylococcus aureus, Escherichia coli, and Candida albicans. The most significant inhibition value was indicated by chloroform extract 1%, where the inhibition value against S. aureus, E. coli, and C. albicans was 82±0.01%; 85.8±0.01%; 85±0.01%, respectively. From these results, O. typhae powder can be developed as a wound medicine through its antibacterial and antifungal activity.